2011
DOI: 10.1523/jneurosci.2127-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Interaural Time Difference in the Owl's Coincidence Detector Neurons

Abstract: Both the mammalian and avian auditory systems localize sound sources by computing the interaural time difference (ITD) with submillisecond accuracy. The neural circuits for this computation in birds consist of axonal delay lines and coincidence detector neurons. Here, we report the first in vivo intracellular recordings from coincidence detectors in the nucleus laminaris of barn owls. Binaural tonal stimuli induced sustained depolarizations (DC) and oscillating potentials whose waveforms reflected the stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
148
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(163 citation statements)
references
References 50 publications
11
148
0
Order By: Relevance
“…Note the standard deviations of about 200 µs in these early recordings of latency. Our current recordings support the hypothesis that within NL, latencies vary by multiples of 2π, and may be precisely regulated at a fine time scale, in order to create a cycle by cycle representation of the stimulus at the point(s) of coincidence detection (Funabiki et al 2011;Ashida et al 2013). Modulation by multiples of 2π is also consistent with cross-correlation and spike timing dependent plasticity models (Gerstner et al 1996;Kempter et al 1998;Pena and Konishi 2000;Fischer et al 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Note the standard deviations of about 200 µs in these early recordings of latency. Our current recordings support the hypothesis that within NL, latencies vary by multiples of 2π, and may be precisely regulated at a fine time scale, in order to create a cycle by cycle representation of the stimulus at the point(s) of coincidence detection (Funabiki et al 2011;Ashida et al 2013). Modulation by multiples of 2π is also consistent with cross-correlation and spike timing dependent plasticity models (Gerstner et al 1996;Kempter et al 1998;Pena and Konishi 2000;Fischer et al 2008).…”
Section: Discussionsupporting
confidence: 84%
“…There is strong evidence in birds and reptiles for the canonical Jeffress model (1948), in which a counter-current organization of ipsilateral and contralateral projections to the nucleus laminaris (NL) converts a temporal code into a place code through delay-line coincidence detection (Carr and Konishi 1990;Carr et al 2009;Funabiki et al 2011). By contrast, binaural projections to the mammalian medial superior olive (MSO) do not appear to include delay lines (McAlpine and Grothe 2003;Smith et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In birds and reptiles, ITDs are analyzed through delay-line coincidence detection of binaural excitatory inputs (Carr and Konishi 1990;Carr et al 2009;Funabiki et al 2011). In mammals, ITD detection also relies on coincidence detection of binaural excitatory inputs, but the mechanistic basis for ITD tuning remains controversial and cannot be explained by axonal delay lines (Brand et al 2002;Grothe et al 2010;McAlpine and Grothe 2003;Roberts et al 2013;van der Heijden et al 2013).…”
mentioning
confidence: 99%
“…Human FFR waveform morphology is affected by stimuli with ITDs (Ballachanda and Moushegian 2000), and FFR amplitude unmasking to BMLD stimuli has been reported (Wilson and Krishnan 2005). In addition, physiological and modeling studies in the nucleus magnocellularis and nucleus laminaris of the barn owl have examined an intracellular membrane potential that oscillates at the stimulus frequency (e.g., 500 Hz) and has been termed the Bsound analog potential^ (Ashida et al 2013a;Ashida et al 2013b;Ashida et al 2012;Funabiki et al 2011). These studies have shown that rate-ITD functions and sound analog potential amplitude-ITD functions demonstrate similar trends (Ashida et al 2013a;Ashida et al 2012;Funabiki et al 2011); sound analog potential amplitude is directly proportional to average firing rate of nucleus laminaris neurons (Funabiki et al 2011).…”
Section: Neurophonics and Binaural Processingmentioning
confidence: 99%